Pengaruh Layanan Bimbingan Kelompok Dengan Teknik Talking Chip Terhadap Kecanduan Gadget Pada Siswa Kelas VIII Di SMP Maria Goretti Semarang - Dinda Putri Arsielia; Fitriana, Siti; Ajie , G. Rohastono (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2025)
Gadget addiction is a behavior of interest in mobile phones accompanied by a lack of control and has a negative impact on individuals. This study aims to determine the effect of group guidance services with the talking chip technique on gadget addiction represented by students of Maria Goretti Semarang Middle School class VIII. The method used in this study is quantitative research with a true experimental type with a pretest-posttest control group design model, using a questionnaire with a Likert scale. The initial condition regarding students' gadget addiction was known to be 34% in the low category and 66% in the high category. After being given group guidance services with the talking chip technique, 93% were in the high category and 7% were in the very high category. The results of the study showed that group guidance services with the talking chip technique can affect students' gadget addiction. It can be concluded that there is a significant influence on gadget addiction of Maria Goretti Semarang Middle School class VIII students before and after group guidance services with the talking chip technique were carried out.